High-quality organohalide lead perovskite films fabricated by layer-by-layer alternating vacuum deposition for high efficiency photovoltaics. (14th February 2017) - Tavakoli, Mohammad Mahdi; Simchi, Abdolreza; Mo, Xiaoliang; Fan, Zhiyong
Abstract : Fabrication of efficient perovskite solar cells (with a high fill factor) using layer-by-layer alternating (LBLA) vacuum deposition with highly crystalline and uniform perovskite films. Abstract : Herein, we present, for the first time, a new procedure to fabricate stoichiometric, uniform, and highly crystalline lead perovskite thin films based on a multi-step vapor deposition technique. In this process, the perovskite film is prepared by layer-by-layer alternating (LBLA) vacuum deposition of PbI2 and methylammounium iodide (MAI). In comparison to the common two-step deposition (TSD) approach, the novel LBLA evaporation process yields thin films with much improved uniformity in terms of composition, morphology, and surface quality. X-ray photoelectron spectroscopy and inductively coupled plasma mass spectrometry show that the I/Pb ratio of the LBLA film is 2.92 ± 0.03, which indicates a more precise stoichiometric composition of organometallics as compared with TSD with an I/Pb ratio of 2.76 ± 0.06. X-ray diffraction and time-resolved photoluminescence measurements also demonstrate higher crystallinity and a longer lifetime for the LBLA films, as compared with the films fabricated by the conventional TSD method. Atomic force microscopy indicates 36% improvement in the surface smoothness as well. The better film quality leads to ∼20% improved power conversion efficiency in bulk heterojunction solar devices, primarily owing to a higher fill factor and current density.